2016
DOI: 10.1111/cmi.12615
|View full text |Cite
|
Sign up to set email alerts
|

‘Strengthening the fungal cell wall through chitin-glucan cross-links: effects on morphogenesis and cell integrity’

Abstract: SummaryThe cross-linking of polysaccharides to assemble new cell wall in fungi requires transglycosylation mechanisms by which preexisting glycosidic linkages are broken and new linkages are created between the polysaccharides. The molecular mechanisms for these processes, which are essential for fungal cell biology, are only now beginning to be elucidated. Recent development of in vivo and in vitro biochemical approaches has allowed characterization of important aspects about the formation of chitin-glucan co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 80 publications
(136 reference statements)
1
81
0
2
Order By: Relevance
“…Comparative genomic and proteomic analyses of ascomycete fungal species have identified six families of conserved, GPI proteins: Sps2, Gas/Gel, Dfg, Plb, Crh, and Yps (79,96). The Sps2 and Dfg5 families are involved in cell wall construction, and the Crh family is involved in cross-linking β-(1,6) glucan and chitin (97)(98)(99).…”
Section: Transglycosidasesmentioning
confidence: 99%
“…Comparative genomic and proteomic analyses of ascomycete fungal species have identified six families of conserved, GPI proteins: Sps2, Gas/Gel, Dfg, Plb, Crh, and Yps (79,96). The Sps2 and Dfg5 families are involved in cell wall construction, and the Crh family is involved in cross-linking β-(1,6) glucan and chitin (97)(98)(99).…”
Section: Transglycosidasesmentioning
confidence: 99%
“…However, lacking direct evidence for enzyme-mediated plasticity at the hyphal apex, some researchers suggested that hyphal tip growth does not involve hydrolytic enzymes; instead, they hypothesized that the new synthesized wall is initially plastic at the growing hyphal apex until it is made rigid at the nongrowing hyphal zone behind the apex by cross-linkage between chitin and ␤-glucan chains (39). Because deletion of a single chitinase gene in different fungal species (40)(41)(42)(43), even all five endochitinase genes in Aspergillus fumigatus (44), Chi1 to Chi5, did not result in apparent growth defects, except for one report that deletion of the chitinase Chit-1 gene in Neurospora crassa leads to a reduction in hyphal growth (45), some researchers concluded that chitinases may have only minor effects on hyphal tip growth (46), whereas other scientists attributed the lack of phenotype in the deletion mutants to redundancy between many members within the chitinase family (7,8). In contrast, Saccharomyces cerevisiae has only two chitinases, Cts1 and Cts2 (8,47), and knockout of the Cts1coding gene leads to a defect in yeast cell separation and the formation of yeast cell aggregates due to the existence of chitin in the yeast primary septum, indicating that chitinases function at sites at which hydrolysis of the cell wall is necessary.…”
Section: Figmentioning
confidence: 99%
“…All of them exhibited similarly transverse cellulose microfibrils (53). However, the chitin microfibrils in fungal cell walls are covalently linked to the nonreducing end of ␤-glucans (7,9,10,54); therefore, only hydrolysis can disrupt this covalent cross-linkage between chitin microfibrils and ␤-glucans to induce fungal cell wall extension.…”
Section: Figmentioning
confidence: 99%
“…This suggests that either the cell wall of S. occidentalis does not contain chitin, or that chitinase is not produced by T. harzianum in sufficient quantity to be detected by LC-MS/MS. The latter is more likely as chitin is expected to be present in the cell wall of S. occidentalis, based on the robustness of S. occidentalis cell wall and the fact that chitin is known to contribute to the strength of cell walls (Arroyo et al 2016;Lamers et al 2016). Moreover, chitin is found in many fungal cell walls such as Candida sp., and as Schwanniomyces sp.…”
Section: Discussionmentioning
confidence: 99%